2021
DOI: 10.1093/heapol/czab032
|View full text |Cite
|
Sign up to set email alerts
|

Is criminalization the answer? Perspectives of community members and police on menstrual seclusion policy in Far-West Nepal

Abstract: Chhaupadi is a form of menstrual seclusion practiced in Nepal in which women and girls are isolated during their menstrual cycles and follow numerous restrictions. The tradition dates back centuries and can have serious physical and mental health consequences. While the practice was criminalized in 2017 with fines and jail time, this legislative action comes after more than a decade of legal history, from an initial ban in 2006, to declaring it a form of violence against women in 2009, and finally, its crimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi . The participants in qualitative studies ranged between three to 81.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi . The participants in qualitative studies ranged between three to 81.…”
Section: Resultsmentioning
confidence: 99%
“…In the chhaupadi practice, which we used as a measure of extreme seclusion, women are secluded and forced to stay separately in makeshift huts or animal sheds during menstruation. The practice has been described in greater detail elsewhere [2529]. Briefly, the practice is rooted in patriarchy and Hindu mythology that considers women impure, thus untouchable, during menstruation and childbirth.…”
Section: Methodsmentioning
confidence: 99%
“…The practice has been described in greater detail elsewhere [25][26][27][28][29]. Briefly, the practice is rooted in patriarchy and Hindu mythology that considers women impure, thus untouchable, during menstruation and childbirth.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, in 2017, the government criminalized the practice, specifying fines and jail time for perpetrators through a criminal code. However, the enforcement of this criminal code remain weak, and a recent study has found that knowledge about the criminal code is extremely low in communities where chhaupadi is practiced [9].…”
Section: Introductionmentioning
confidence: 99%